Nurse's tasks in nutritional treatment of patients in critical condition - Anna Maria Kostka; Sylwia Anna Krzemińska; Karolina Pracuk; Szymon Czerniawski; Malwina Janas; Adriana Milena Borodzicz (Kazimierz Wielki University, 2017)
Malnutrition is diagnosed in more than half of patients admitted to hospitals. Lack of individual nutrients leads to many complications, which are especially aggravated in patients in critical condition with multiple organ failure. The aim of nutritional treatment of patients in critical condition is to ensure the smooth circulation, ventilation, excretion and metabolic disorders. Dietary treatment is a standard procedure that should be incorporated as soon as possible. Patients may receive enteral or parenteral food. No matter what route of supply is chosen, each patient must be properly prepared. The role of the physician is to assess the degree of nutrition, nutrient requirements, the choice of ingredients, the dosage and the method and route of administration. The nurses tasks is to prepare and supply the prescribed formulations, to observe the patient throughout the feeding period, to control the basic parameters and to observe the complications which can appear because of nutrition. Relationship between doctor and nurse is very important during patients feeding. A good cooperation in medical team leads to patients quicker recovery.